2010
DOI: 10.1029/2009jc005870
|View full text |Cite
|
Sign up to set email alerts
|

A note on Doppler processing of coherent radar backscatter from the water surface: With application to ocean surface wave measurements

Abstract: [1] The technique for extracting wave period and wave direction from radar backscattering intensity is well developed, but the determination of spectral density or wave height is hindered by the complex nature of the modulation transfer function. In contrast to backscattering intensity, the Doppler signal of a coherent radar is originated from the radial velocity of the scattering objects. Its oscillatory component is contributed by ocean waves. The peak component of the Doppler velocity spectrum can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Assuming that wave breaking and the incidence angle dependence are small, linear wave theory can be applied to transform the orbital velocity spectrum to a wave amplitude spectrum. Hwang et al (2010) showed that peak frequencies and wavelengths can be estimated reasonably well, while the integral spectral energy differs considerably from the one retrieved by a buoy. The authors attributed this to various non-trivial uncertainties, including directional distribution, shadowing effect, radar look direction with respect to wave propagation, swell modification and difference between spatial and temporal measurements.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Assuming that wave breaking and the incidence angle dependence are small, linear wave theory can be applied to transform the orbital velocity spectrum to a wave amplitude spectrum. Hwang et al (2010) showed that peak frequencies and wavelengths can be estimated reasonably well, while the integral spectral energy differs considerably from the one retrieved by a buoy. The authors attributed this to various non-trivial uncertainties, including directional distribution, shadowing effect, radar look direction with respect to wave propagation, swell modification and difference between spatial and temporal measurements.…”
Section: Resultsmentioning
confidence: 89%
“…With this accuracy, the proposed method performs at least as well as the best results using traditional methods, however, without the need for any calibration and sophisticated filtering techniques (Nieto-Borge et al, 1999;Vincent Bueno et al, 2012). In the following, the results are compared to the method suggested by Hwang et al (2010) and discussed with respect to the physical explanation of this purely empirical relationship. For this, the geophysical interpretation of the Doppler signal from the ocean surface has to be discussed briefly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations